Environmentalism and Eco-Criticism in the Poetry of Keki N. Daruwalla: Exploring Keki N Daruwalla's poetry through an ecocritical lens (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The world of literature while working with the beauty and power of nature is always painted environmental concerns and the threat posed by the continued abuse of our environment humanity has recently attracted the attention of writers. It’s a sense of anxiety and its reference to the literature which gave the new branch of literary theory, namely Ecocriticism.Nature has been the talk of the town for a variety of art forms and management, especially in poetry Indian poets like kake N Daruwalla, Sarojini Naidu, A.K.Ramanujan, Dilip Chitre and many more have celebrated various aspects of nature for different and emerging purposes and from different views. Their treatment of environment points out how environment acquires dissimilar understanding and connotation. Occasionally it is considered as a divine spirit, a holy mother and friend of man and the other hand it plays the role of an aggressive power that acts as a supernatural entity to penalize human beings for their wrong conducts. In any affair, nature creates an outstanding part of the thematic and artistic elements in poetic discourses. Various elements of Environment including the river, sky, plants, animals, and creatures often find symbolic value that rewards the complexity of the creation of poetry and enhances its texture. The paper seeks to explore Keki N Daruwallas poetry in Indian English literature and his work from an ecocritical perspective.